Evaluasi Tata Kelola Rumah Sakit Badan Layanan Umum pada 4 Rumah Sakit Vertikal Kelas A di Jawa dan Bali - Partakusuma, Lia G. (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2014)
A hospital as an institution needs to implement good corporate governance and good clinical governance to improve service quality continuously. Public Service Agency (BLU) is a government agency established in order to provide services to the community in the form of supply of goods and/or services being sold without profit and doing activities based on the principles of efficiency and productivity. The government realized the needs for flexibility in healthy business practices of various institution, so it has issued Government Regulation No. 23, 2005 (PP 23/2005) of the Financial Management BLU and allow its application to be implemented in a variety of government agencies including the hospitals. The purpose of this research is to evaluate governance at four (4) type A vertical hospitals in Java and Bali. There are differences in the implementation. These include differences in achievement of the completeness document on good corporate governance as well as governance requirements documents as well as differences in the 4 (four) elements of governance from PP 23/2005 that includes 12 (twelve) related factors of Donabedian1.a and Glickman’s2.a scheme: corporate culture, BLU establishment, hospital by laws,strategic planning & business plan budget, service development, procurement of goods and services, service standards, tariffs, management officer, remuneration, staffing, training and supervision. This research suggested the need for improved understanding of work force management officer, the quality of guidance and supervision, the establishment of specialized managers in BLU in Ministry of Health, the establishment of an integrated team involving all stakeholders. Improvements needed in change organizational culture, BLU’s hospital selection & evaluation, BLU’s institutional requirements, reward & punishment system, clear rules and strategic plan & business plan budget. Appropriate public policy to determine the success of a country in achieving its objectives is needed.